Three Dynamical Evolution Regimes for Coupled Ring-satellite Systems and Implications for the Formation of the Uranian Satellite Miranda - Andrew J. Hesselbrock; David A. Minton (The Astronomical Journal)
In coupled ring-satellite systems, satellites exchange angular momentum with both the primary through tides and the ring through Lindblad torques, and may exchange material with the ring through accretion and tidal disruption. Here we show that these coupled ring-satellite systems fall into three distinct dynamical regimes, which we refer to as “Boomerang,” “Slingshot,” and “Torque-dependent.” These regimes are determined by the relative locations of the fluid Roche limit, the synchronous orbit, and the maximum orbit in which Lindblad torques can perturb a satellite. Satellites that accrete from rings in the Boomerang regime remain interior to the synchronous orbit, and may be driven back toward the primary by tides. Satellites that accrete from rings in the Slingshot regime form exterior to the synchronous orbit, and are always driven away from the primary. Satellites that accrete from rings in the Torque-dependent regime may exhibit either Boomerang or Slingshot behavior, depending on ring and satellite masses. We consider both known and hypothesized ring-satellite systems in the solar system, and identify which of these three regimes they fall into. We determine that Uranus exists within the Torque-dependent regime. Using the RING-MOONS code, which models the dynamical evolution of coupled ring-satellite systems, we show that the Uranian satellite Miranda may have accreted from a massive ancient Roche-interior ring and followed a Slingshot-like dynamical path to its present orbit beyond the synchronous orbit, while satellites that accreted after Miranda followed Boomerang-like evolutionary paths and remained interior to the synchronous orbit.